ANALISIS STRATEGI BERSAING INDUSTRI BISNIS FARMASI/APOTEK DI KOTA PEKANBARU - ", Prawiades; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This competition resulted pharmacy business trying to get consumers by way of competitive strategy and maintain its superiority. Many ways out were done in maintaining the pharmacy business by the managers such as creating competitive strategy.The Policy strategy of competing pharmacies in Pekanbaru using one variable Differentiation Strategy, Strategy focus, Overall Cost Leadership.Competitive strategy on Differentiation Strategy variables were indicators into the unique product received good feedback from respondents, while the different indicators in the perception of consumers received a Very Good response. In the Overall Cost Leadership Strategy variables, there were indicators of the ability to have a guaranteed raw material suppliers and different in a dominant market position or have a substantial capital got very good feedback from respondents. While the focus strategy that had a small segment of group indicator within the industry concerned and complete its strategy to serve them by setting aside others received Very Good responses.Keywords: Pharmacy Competitive Strategy, Pharmacy Business Industry in Pekanbaru city